Penerapan Teknologi Mesin Press Baglog dan IoT untuk Peningkatan Produktivitas serta Pemasaran Digital pada UMKM Budidaya Jamur - Akhmad Jayadi; Fauzi Ibrahim; Lestari Wibowo; Silvia Nanda Agustin; Muhammad Akbar Husni Harun; Raffi Ramadhan Oktaviansyah (Universitas Negeri Gorontalo, 2026)
Tani Makmur, a micro, small, and medium enterprise (MSME) located in Simbaringin Hamlet, Sidosari Village, South Lampung Regency, faces challenges in production efficiency, cultivation environment control, and market reach. The manual baglog production process limits productivity, while conventional marketing restricts business growth and competitiveness. This community service program aims to enhance productivity, efficiency, and market expansion through the application of appropriate technology and digital strategies. The implementation methods included socialization, technical training on the use of an automatic baglog press machine, the application of Internet of Things (IoT) technology for real-time monitoring of temperature and humidity in the mushroom house, and digital marketing training utilizing social media and e-commerce platforms. Evaluation was conducted using questionnaires and analysis of productivity data before and after the program. The results showed an increase in production capacity from 50 to 100 baglogs per day, a 60% rise in social media engagement, and a 40% growth in sales. The program also improved participants’ understanding and skills in operating the machine, utilizing IoT systems, and implementing digital marketing strategies. Therefore, the integration of the baglog press machine and IoT technology combined with digital marketing training proved effective in enhancing the competitiveness and sustainability of mushroom cultivation MSMEs.